The Effect of Financial Liberalisation on Financial Sector Development in The Gambia: fianncial liberalisation - Jaabi, Seeku A K; Barrai, Micheal (Advances in Social Sciences Research Journal, 2019)
The Gambia started its financial liberalisation policies in the mid-1980s with a number of structural and institutional reforms resulting to a marked improvement in the financial sector. The study attempts to establish whether the reforms undertaken have increased financial intermediation thus impacting on financial deepening in the country. The methodology made use of various variables and macro-economic indicators to test the relationship between financial intermediation and financial deepening in an economy, applying stepwise least squares regression method. The study found that The Gambian financial system though shallow, has reported significant improvements over the years compared to the commencement of the reforms in the 80s. Results revealed that improvements in the rule of law, structural reforms, legal enforcements, regulatory reforms and diversification have increased intermediation and help boost the banking and financial system in The Gambia. The economy performed better after these improvements with diversified financial systems including microfinance, licensed bureaus, expansion in insurance companies including Islamic insurance – Takaful.